Benefits of using fiber post and core to restore decaying teeth: a case report and analysis - Patil, Sujeet K.; Jain, Saloni S. (International Journal of Research in Medical Sciences, 2024)
The post and core approach works best for treating teeth with short clinical crowns that are insufficiently strong to sustain the final restoration. The widespread acceptance of fibre posts can be attributed to their advantages over traditional metallic post materials. Additionally, fibre posts' mechanical and aesthetic advantages have given them popularity in the dental industry. Additionally, the outcomes of a few clinical trials have given therapists confidence to employ the fibre posts. For the previous six months, the primary complaint of a 23-year-old guy had been decaying teeth in the upper front area. On both sides of the maxillary central and lateral incisors, deep proximal caries was discovered. Because of the poor remaining crown structure and crown placement, the proposed course of treatment involved root canal therapy for all four teeth, followed by post and core for 11, 21, and 22. One of the many problems caused by anterior teeth decay is appearance. When such teeth are restored with glass fibre posts as opposed to the more traditional post core technique, the patients have better results over an extended period of time with fewer appointments. Glass fibre restorations, as opposed to the more conventional post core procedure, yield superior outcomes over a longer length of time and require fewer consultations.